Formate Is Required for Growth of the Thermophilic Acetogenic Bacterium Thermoanaerobacter kivui Lacking Hydrogen-Dependent Carbon Dioxide Reductase (HDCR) - Jain, Surbhi; Dietrich, Helge M.; Müller, Volker; Basen, Mirko (Frontiers in Microbiology, 2020)
The hydrogen-dependent carbon dioxide reductase is a soluble enzyme complex that directly utilizes hydrogen (H2) for the reduction of carbon dioxide (CO2) to formate in the first step of the acetyl-coenzyme A- or Wood-Ljungdahl pathway (WLP). HDCR consists of 2 catalytic subunits, a hydrogenase and a formate dehydrogenase (FDH) and two small subunits carrying iron-sulfur clusters. The enzyme complex has been purified and characterized from two acetogenic bacteria, from the mesophile Acetobacterium woodii and, recently, from the thermophile Thermoanaerobacter kivui. Physiological studies towards the importance of the HDCR for growth and formate metabolism in acetogens have not been carried out yet, due to the lack of genetic tools. Here, we deleted the genes encoding HDCR in T. kivui taking advantage of the recently developed genetic system. As expected, the deletion mutant (strain TKV_MB013) did not grow with formate as single substrate or under autotrophic conditions with H2+CO2. Surprisingly, the strain did also not grow on any other substrate (sugars, mannitol or pyruvate), except for when formate was added. Concentrated cell suspensions quickly consumed formate in the presence of glucose only. In conclusion, HDCR provides formate which was essential for growth of the T. kivui mutant. Alternatively, extracellularly added formate served as terminal electron acceptor in addition to CO2, complementing the growth deficiency. The results show a tight coupling of multi-carbon substrate oxidation to the WLP. The metabolism in the mutant can be viewed as a coupled formate+CO2 respiration, which may be an ancient metabolic trait.